Peningkatan Pelayanan Publik Melalui Pelatihan Administrasi di Desa Sumber Makmur Kabupaten Banjar - Nur Tinri, Muh. Darwis; Gunawan, Hendra; Nuddin; Rahman; Tamrin, Usman; Rosmiati, Etty; Wahid, Abdul (Universitas Pejuang Republik Indonesia, 2025)
This community service aims to improve the quality of public services in Sumber Makmur Village, Banjar District through administrative training for village officials. The method of implementing the activity includes needs analysis, program socialization, intensive training for 12 sessions, and mentoring for 4 months to 25 village officials with a participatory approach and direct practice. The results of the activity showed a significant increase in the capacity of village officials in administrative management, a 35% increase in service speed, a reduction in administrative errors by up to 60%, and an increase in community satisfaction from 62% to 87%. Training and mentoring have proven to be effective in improving administrative competence and professionalism of village officials. Challenges such as limited digital infrastructure and the need for advanced training still need to be addressed to ensure the sustainability of public service transformation. In conclusion, village administration training is a strategic solution to improve the quality of public services which leads to increased public trust in the village government, with recommendations for strengthening the administrative system through policy support and cross-sector collaboration.